Aplikasi Metode Job Safety Analysis Dan Pendekatan HIRADC Untuk Analisis Risiko Keselamatan Dan Kesehatan Kerja Pada Penambangan Bawah Tanah Bijih Emas Pt. Dempo Maju Cemerlang Pesisir Selatan - Nia Kurniasih; Fadhilah Fadhilah; Andri Prihatanto (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. PT. Dempo Maju Cemerlang is one of the gold mining companies that implement underground mining system. Because judging from the risk management there are still potential hazards in the company, this study aims to find out the potential hazards in some areas of work that can cause accidents, statistics of work accidents frequency rate and severety rate,as well as reveal hazard control in the form of Job Safety Analysis (JSA) and Hazard Identification, Risk Assessment And Determining Control (HIRADC). Data collection techniques using questionnaire questionnaires, interviews, and observations of work activities. The results of analysis of the risk level of the sub-criteria that often occur in the overall at PT. Dempo Maju Cemerlang based on the percentage calculation is 26% pale finger discoloration during jeck legoperation, 10% hit in restricted areas, pinched tools, and 78% muddy or flooded roads. Work accidents with a frequency rate in 2019 of 44.18 and a severity of 166.55. JSA and HIRADC are used to identify work hazards in the main hole SOD (South Ore Drift) in the work of drill machine jack leg, rock bolt installation, railmounting, shovel rocker operation, locomotive operation and Granby.Keywords: Jack leg drillmachine, rock bolt installation, railmounting, shovel rocker operation, locomotive operation and Granby.